Hubungan Perilaku Masyarakat dengan Penyakit Malaria di Puskesmas Koya Barat, Distrik Muara Tami, Kota Jayapura - Konstantina Marthina Pariaribo (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Malaria is an infectious disease caused by Plasmodium sp which is transmitted by the Anopheles mosquito. The spread and endemicity of malaria is greatly influenced by the existence of breeding sites for Anopheles mosquitoes as a result of human behavior. Papua still has the highest malaria endemic status in Indonesia. West Koya Community Health Center, based on data from the Jayapura City Health Service, has the highest number of malaria cases with the highest API figure of the 13 Community Health Centers. The aim of the research was to determine the influence of community behavior on malaria at the Koya Barat Health Center. This type of analytical research uses a crosectional study. The population is 14,442 people who visited the Koya Barat Health Center in 2022, with a sample size of 100 people calculated based on the Slovin formula. Data were analyzed bivariately using the chi square test and risk factor analysis calculating prevalence ratio (RP) values ​​with confidence intervals (CI 95%). Based on the results of the chi square test, it was found that the knowledge variable had an influence with a ρ-value = 0.049 ≤ 0.05, meaning that there was an influence of the respondent's knowledge on the incidence of malaria. Risk analysis obtained RP = 1.441; 95% CI (0.783 – 1.854) which is interpreted to mean that respondents with poor knowledge have a 1.144 times chance of suffering from malaria compared to respondents with good knowledge but it is not significant because the lower and upper values ​​exceed 1. Meanwhile, the results obtained for the attitude and action variables have no effect on However, malaria is a risk factor because the RP value is > 1 but is not significant because the 95% CI exceeds 1.